Pengaruh Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Kelas V SD Negeri Percontohan - Yunita Sihite; Lisbet Novianti Sihombing; Desi Sijabat (Departement of Mathematics Education, 2023)
This study aims to determine the condition of the school environment at SD Negeri Pilot Pematangsiantar, to find out whether there is a significant influence between the school environment on the learning motivation of fifth grade students at SD Negeri Pilot Pematangsiantar. The method used in this research is a quantitative approach. Where the sample consisted of 30 students, namely class V SD. The data collection technique uses a questionnaire while to analyze the data using the t test formula and descriptive statistics. The results of this study based on data analysis found that the school environment at Pilot Pematangsiantar Public Elementary School based on the results of the f test it is known that the significant value for the effect of variable (x) simultaneously on (y) is 0.00 <0.05 and the calculated f value is 27.947 > 2.048 so that it can be interpreted that there is a significant influence between the school environment on learning motivation with a significant value of 0.00 by comparing it using a significance level using 0.05. then Ho is rejected, meaning that there is a significant influence between the school environment on the learning motivation of fifth grade students at SD Negeri Pilot Pematangsiantar.